Pola Asuh Panti Asuhan An-Nur Pasanehan Dalam Membentuk Moral di Kecamatan Canduang - Silfi Maya Dwita; Yeni Afrida; Sri Hidayati (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
Research with the title Parenting Pattern of An-Nur Pasanehan Orphanage, Canduang Dalam District. Shaping Morals. Orphanage parenting style. In Forming children's morals is a person who has the ability and expertise that is educational, fostering, directing, assessing and evaluating children in orphanages. This research is qualitative with a descriptive approach, with data collection through observation and interviews. Data analysis techniques with data reduction, data display and data verification. The research aims to find out how the upbringing style of the An-Nur Pasanehan orphanage in Canduang District forms morals. The informants from this study consisted of several children who supported the results of this study, namely the existence of parenting patterns that shaped children's morals.